Utilizing "Interactive Labs" Technology Resources in Science Learning: A Literature Review - Verawati, Ni Nyoman Sri Putu; Rokhmat, Joni; Sukarso, AA; Harjono, Ahmad; Makhrus, Muh (International Journal of Essential Competencies in Education, 2024)
Science education is widely recognized as crucial for equipping students with the necessary skills to navigate the complexities of the modern world. In response to the changing educational landscape, the integration of Interactive Labs technology resources has emerged as a promising strategy to enhance science learning experiences. This literature review aims to provide insights into the benefits, challenges, and emerging trends associated with the use of Interactive Labs in science education. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology, this review systematically identified 35 relevant studies from the SCOPUS database. The findings highlight the transformative potential of Interactive Labs in promoting active learning, addressing accessibility issues, and catering to diverse learning styles and paces. Specifically, Interactive Labs have been found to improve students' understanding of complex scientific concepts, increase their engagement in the learning process, and provide personalized learning experiences tailored to individual needs. However, despite these advantages, challenges persist, including concerns about the authenticity of the learning experience, technical issues, and the need for sufficient teacher training. To advance the field of technology-enhanced science education, future research should consider expanding search criteria, utilizing mixed-methods approaches for comprehensive analysis, conducting longitudinal studies to track long-term impacts, and ensuring equal access to Interactive Labs for all students. By addressing these recommendations, stakeholders can collaborate to maximize the benefits of Interactive Labs, ultimately advancing science education to be more engaging, accessible, and effective for all students.